Reliable file sharing scheme for mobile peer-to-peer users using epidemic selective caching - Mavromoustakis, Constandinos X.; Karatza, Helen D. (My University, 2005)
In the recent years, mobility is gaining popularity for non critical civilian applications. Hybrid and pervasive computing environments with billions of users, devices, and services, demand ensured end to end reliability and integrity. However due to the asymmetry in wireless communication and the scarceness of wireless resources, the use of such networks as a mean of file sharing is not always successful. This paper proposes an approach for reliable file sharing based on the advantages of epidemic selective dissemination through fixed and mobile infostations. The proposed scheme attempts to fill the gap between mobility and reliable file sharing for mobile peer to peer users. Facing the problem of flooding this method successfully enables end to end reliability by forwarding requested packets to epidemically 'selected' users in the network. Thorough examination is made for the performance and reliability of the epidemic selective caching method proving it's robustness in reliable file sharing among mobile peers.